PENGETAHUAN ISTRI DAN PENGARUHNYA TERHADAP PENGAMBILAN KEPUTUSAN PENGGUNAAN BIOGAS - Muflikhati, Istiqlaliyah; Yuliati, Lilik Noor; Maulanasari, Rani (Jurnal Ilmu Keluarga dan Konsumen, 2011)
Wife’s Knowledge and Its Influence toward Decision Making of Biogas Using Abstract Biogas is an alternative energy that gives economic and health advantages. However, the study of the knowledge and using of biogas are still limited. This study aimed to analyze the wife's knowledge about biogas and its influence toward decision making of using biogas in the family in the village of Haurngombong, Sumedang Regency, West Java. Families that involved in this study were 60 families that consist of biogas users’ families and biogas nonusers’ families. Data were collected through structured interviews with using questionnaire. Data analysis used the Independent Samples T Test and logistic regression tests. The results showed that the level of knowledge of wife from families who using biogas was higher than nonusers’ families. Knowledge of the wifes and family size had positive effect toward the decision making of biogas using.